Titania‐Based Coral‐Structured Solar Absorber Coating with Improved Scalability and Durability at High Temperature - Yifan Guo; Kaoru Tsuda; Milad Mohsenzadeh; Sahar Hosseini; Yasushi Murakami; Joe Coventry; Juan F. Torres (Advanced Science)
Abstract Solar energy harvesting and storage are essential in the future mix of renewable energy technologies. Hierarchical coral‐structured coatings have been shown to yield high solar absorptance in concentrating solar thermal (CST) systems. However, interfacial delamination and scalability challenges owing to material complexity pose significant hurdles for the widespread industrial adoption of these hierarchical CST coatings. Here, a coral‐structured coating is proposed whose black pigments are strongly bonded by titania, which is a material that mitigates interfacial delamination. Importantly, this coating follows a facile deposition procedure suitable for large‐scale solar receivers. The drone‐deposited coating inhibits cation diffusion and maintains a stable solar absorptance of 97.39±0.20% even after long‐term (3000 h) high‐temperature (800∘C) aging. The scalability of developed coating represents a substantial advancement in the implementation of light‐trapping enhancement and maintenance approaches across a wide range of CST applications.